Interlimb Practice and Aging: Coding a Simple Movement Sequence. - Panzer, Stefan; Gruetzmacher, Nicole; Ellenbürger, Thomas; Shea, Charles H. (Experimental Aging Research)
Background/Study Context: The purpose was to determine if aging interacts with the coding of a simple spatial-temporal movement sequence. Methods: An interlimb practice paradigm (24 participants; 12 young adults [age: 23–29]; 12 old adults [age: 65–78]) was designed to determine the coordinate system (visual-spatial/motor) that is used to code the movement sequence. Practice was scheduled over 2 days involving either the same visual-spatial or the same motor coordinates. On Day 3, two retention tests (Day 1/Day 2) were conducted. Results: Keeping the motor coordinates the same during acquisition resulted in superior retention only for younger adults. Conclusion: The data provide strong evidence that the motor code plays a dominant role in acquiring simple movement sequences for younger adults, but not for older adults.